Revised classification of the subfamily Leishmaniinae (Trypanosomatidae) - Kostygov, Alexei Y; Yurchenko, Vyacheslav (Folia parasitologica, 2017)
In the present study, we critically revised the recently proposed classification of the subfamily Leishmaniinae Maslov et Lukeš in Jirků et al., 2012. Agreeing with erection of the genus Zelonia Shaw, Camargo et Teixeira in Espinosa et al., 2017 and the subgenus Mundinia Shaw, Camargo et Teixeira in Espinosa et al., 2017 within the genus Leishmania Ross, 1908, we argue that other changes are not well justified. We propose to: (i) raise Paraleishmania Cupolillo, Medina-Acosta, Noyes, Momen et Grimaldi, 2000 to generic rank; (ii) create a new genus Borovskyia gen. n. to accommodate the former Leptomonas barvae Maslov et Lukeš, 2010 as its type and only species; (iii) leave the subfamily Leishmaniinae as originally defined, but establish two infrafamilies within it: Leishmaniatae infrafam. n. and Crithidiatae infrafam. n.
Keywords: new infrafamilies; new genera; Borovskyia; Crithidiatae; Leishmaniatae; Paraleishmania; Phylogeny; fylogeneze; Leishmania; taxonomy